Procedural Gaps in Indonesia’s Immigration Policy: An Analysis of the Arrival of Rohingya Refugees in Aceh, 2023–2024 - Ari Gusti Handayani; Muhammad Syahroni Rofii (Green Publisher Indonesia, 2026)
The arrival of Rohingya refugees on the coast of Aceh from November 2023 to October 2024 reveals a procedural vacuum in Indonesia's immigration policy. Although Law No. 6 of 2011 on Immigration and Presidential Regulation No. 125 of 2016 on the Handling of Refugees from Abroad provide a fundamental legal framework, both instruments predominantly regulate the post-landing stage and provide minimal operational direction for the pre-landing phase. This research evaluated the procedural readiness of Indonesia's immigration policy in dealing with refugee arrivals through illegal channels, using Aceh as a case study. Employing a qualitative policy analysis approach, this study utilizes document review and systematic literature review, framed by securitization theory and the concept of procedural readiness. The analysis identified three procedural gaps with significant implications for immigration practices: the ambiguity of immigration involvement at the pre-landing stage, the absence of standard protocols for verifying foreigners entering through illegal channels, and the limitations of joint case management mechanisms with international organizations. The Aceh case demonstrates that unresolved procedural gaps are filled by either ad-hoc initiatives of field apparatus or public pressure outside the official policy framework. Strengthening strategies should focus on internal immigration instruments, including pre-landing operational protocols, verification SOPs for illegal routes, and structured cooperation mechanisms with UNHCR and IOM. This paper contributes to Indonesian immigration literature by emphasizing procedural readiness as an evaluative variable in refugee policies for transit countries.